The art and culture of Scandinavian Central Europe, 1550-1720 - Neville, Kristoffer 19XX- (The Pennsylvania State University Press, 2019)
"Explores early modern Scandinavia as an integral and essential part of Central Europe. Examines the visual arts in all media from the Reformation to the fall of Sweden as a great power in the earlier eighteenth century"--Provided by publisher